Poitrenaud-Lamesi, Brigitte (2023), Immaginari e povertà. San Francesco nella creazione contemporanea, Padova, Edizioni Messaggero, 220 pp. - Linossi, Patrizia (Cuadernos de Filología Italiana, 2024)
The book Imaginaries and poverty. Saint Francis in contemporary creation, written by Brigitte Poitrenaud-Lames and published in 2023 by Messaggero editions, presents a preface by Paolo Grossi. In the four chapters of the volume, preceded by an extensive introduction that traces the rich critical production around Saint Francis, we have the opportunity, not only to retrace various artistic interpretations of this personality and his message, but also to consider how much some characters are actually capable of arising such strong emotions and interests that makes them always subject of further reinterpretations and rediscoveries. This kind of characters is able to become a constant reference point and comparison even in our contemporaneity. Each interpretation proposed in this book highlights one or more aspects of Francis, one or more characteristic. All the interpretations contribute to reiterate the extraordinary strength of the represented subject. A text that represents the saint of Assisi through the gaze of those who were influenced by his message that helps us to observe this multifaceted figure from all possible angles, enriching our perception of him, leading us to a fuller knowledge, albeit not an exhaustive one.